Ti-in-zircon thermometry applied to contrasting Archean metamorphic and igneous systems - Hiess, Joe; Nutman, Allen Phillip; Bennett, Vickie C; Holden, Peter (Research Online, 2008)
Ti-in-zircon thermometry with SHRIMP II multi-collector has been applied to two well-documented Archean igneous and metamorphic samples from southern West Greenland. Zircons from 2.71 Ga partial melt segregation G03/38 formed in a small (<1 >m(3)), closed system within a mafic rock under high pressure granulite facies conditions. Results of 14 Ti analyses present a mean apparent zircon crystallization temperature of 679 +/- 11 degrees C, underestimating independent garnet-clinopyroxene thermometry by 20-50 degrees C but consistent with reduced a(TiO2) in this system. 36 spot analysis on 15 zircons from 3.81 Ga meta-tonalite G97/18, with an estimated magmatic temperature >1000 degrees C, yield a low-temperature focused normal distribution with a mean of 683 +/- 32 degrees C, further demonstrated by high resolution Ti mapping of two individual grains. This distribution is interpreted to represent the temperature of the residual magma at zircon saturation, late in the crystallization history of the tonalite. Hypothetically, Ti-in-zircon thermometry on Eoarchaean detrital zircons sourced from such a high temperature tonalite would present a low-temperature biased image of the host magma, which could be misconstrued as being a minimum melt granite. Multiple analyses from individual zircons can yield complex Ti distributions and associated apparent temperature patterns, reflecting cooling history and local chemical environments in large magma chambers. In addition to inclusions and crystal imperfections, which can yield apparent high temperature anomalies, zircon surfaces can also record extreme (>1000 degrees C) apparent Ti temperatures. In our studies these were traced to (49)Ti (or a molecular isobaric interference) contamination derived from the double sided adhesive tape used in sample preparation, and should not be assigned geological significance. (C) 2007 Elsevier B.V. All rights reserved. Document Type: Article